Study and Characterization of Thermal Comfort in a Desert Climate (Advances in Systems Science and Applications, 2019)
The main objective of this study, it is prose on the characterization of thermal comfort in the new habitable architectures located for a completely desert area. This numerical characterization is intended to determine the parameters that affect the thermal comfort for the occupants of these architectures in this region. To achieve this objective, a numerical model describing the thermal exchanges taking place in a model of a habitable envelope has been developed. This model is based on thermal balances established at the level eachwall of the habitat. The numerical models developed have been validated using climatic data recently measured in the renewable energy research unit of the Saharan medium at Adrar ‘’URER'MS‘’. A well detailed analysis of the some parameters that influence the thermal comfort in this architecture was raised and discussed. The fundamental equations governing thermal exchanges have been concretized by an implicit finite difference method, based on the nodal procedure. The system of algebraic equations obtained was solved by the iterativeGaussian method. The results of the numerical simulation have shown that the material currently used in the construction of this architecture of Adrar region, as well as the current climatological conditions, are the main causes of the thermal discomfort.